Erasmus and International Credit Mobility in a contribution to the Sustainable Development Goals associated with Quality Education and Reducing Inequalities - Saraiva, Margarida (2022)
In Europe, and promoted by the European Commission, the Erasmus+ programme has been providing institutions, through various actions, with mobility and exchanges of students, teachers and non-teaching staff both within and outside Europe. In order to increase the qualitative impact of its actions and to ensure equal opportunities, the programme aims to make it easier to reach more people of all ages and from other cultures, and from diverse social and economic backgrounds. Considering the importance that this programme currently has at global level and its objectives being aligned with the 2030 agenda and given the fundamental characteristics and objectives of the programme and the mobility projects, it became relevant to analyse the contribution to the Sustainable Development Goals associated with quality education (SDG 4) and the reduction of inequalities (SDG 10). The research methodology used the analysis of the programme and Key Action 1 individual mobility for learning purposes objectives’ and more specifically those related to mobilities of higher education participants under the International Credit Mobility (ICM) in the period 2014-2020, crossing them with those of the 2030 Agenda and Sustainable Development Goals 4 and 10. The questionnaires applied to the participants in this action were also analysed and was possible to check the prevalence of SDGs 4 and 10. It was found during the study that Erasmus, and mobility projects, strongly contribute to the Sustainable Development Goals of quality education and reducing inequalities, but that there are also other SDGs to which Erasmus can contribute and are certainly worth evaluating.